GAMBARAN KEPUASAN PASIEN TERHADAP PELAYANAN KEFARMASIAN BERBASIS SYARIAH DI APOTEK MARGAHUSADA SEMARANG - Atma Rulin Dewi N; Visi Ashari Anhar; Sri Rahayuni (Nusantara Hasana Journal, 2025)
Pharmaceutical services have an important role in health efforts to eliminate symptoms of a disease, prevent disease, and can cure disease, conversely, less than optimal pharmaceutical services can cause harm to patients. Patient satisfaction is a product if consumed can provide what the patient needs, wants and hopes can all be fulfilled after consuming the product. Service quality has five dimensions, the five dimensions are physical evidence, reliability, responsiveness, assurance, and empathy. Therefore, the results obtained can provide consumer satisfaction and have an impact on consumer or patient trust in that place and have an impact on repeat purchases, loyalty and positive effects. Based on the results of the study regarding the description of patient satisfaction with pharmaceutical services at the Margabusada Semarang Pharmacy, it can be concluded that in general patients are satisfied with the services provided by pharmacists. This is indicated by the results of the percentage of respondents who stated that they were satisfied by 18.7% and very satisfied by 14.7%, which when combined shows that 33.4% of respondents have a positive level of satisfaction with pharmaceutical services. Meanwhile, only 2.6% of respondents expressed dissatisfaction with the service received.